Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1111/jpy.13340
|View full text |Cite
|
Sign up to set email alerts
|

Formal recognition of host‐generalist species of dinoflagellate (Cladocopium, Symbiodiniaceae) mutualistic with Indo‐Pacific reef corals

Abstract: The existence of widespread species with the capacity to endure diverse, or variable, environments are of importance to ecological and genetic research, and conservation. Such “ecological generalists” are more likely to have key adaptations that allow them to better tolerate the physiological challenges of rapid climate change. Reef‐building corals are dependent on endosymbiotic dinoflagellates (Family: Symbiodiniaceae) for their survival and growth. While these symbionts are biologically diverse, certain gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 80 publications
1
21
0
Order By: Relevance
“…Here we defined a TD block as a block comprising two or more consecutive genes with high sequence identity on a genome scaffold. In our independent survey of TD genes in all 19 available Suessiales genomes, we found the largest number and proportion of TD genes in the freeliving lineages of P. glacialis (7.8% in CCMP1383, 9.2% in CCMP2088) and S. natans (7.1%), followed by the symbiotic S. tridacnidorum CCMP2592 (6.5%) and C. proliferum SCF055 (6.0%; this taxon was formerly described as Cladocopium goreaui SCF055 [29]), with smaller proportions observed in the freeliving E. voratum (3.9% in rt-383, 4.4% in RCC1521), and the smallest in S. microadriaticum (1.0-2.2%) (table 1). Some of the largest TD blocks consisted of 13-16 genes, found in genomes of free-living lineages (S. natans, and the P. glacialis CCMP1383 and CCMP2088).…”
Section: Genomes Of Free-living Species Contain a Larger Number Of Ta...mentioning
confidence: 92%
“…Here we defined a TD block as a block comprising two or more consecutive genes with high sequence identity on a genome scaffold. In our independent survey of TD genes in all 19 available Suessiales genomes, we found the largest number and proportion of TD genes in the freeliving lineages of P. glacialis (7.8% in CCMP1383, 9.2% in CCMP2088) and S. natans (7.1%), followed by the symbiotic S. tridacnidorum CCMP2592 (6.5%) and C. proliferum SCF055 (6.0%; this taxon was formerly described as Cladocopium goreaui SCF055 [29]), with smaller proportions observed in the freeliving E. voratum (3.9% in rt-383, 4.4% in RCC1521), and the smallest in S. microadriaticum (1.0-2.2%) (table 1). Some of the largest TD blocks consisted of 13-16 genes, found in genomes of free-living lineages (S. natans, and the P. glacialis CCMP1383 and CCMP2088).…”
Section: Genomes Of Free-living Species Contain a Larger Number Of Ta...mentioning
confidence: 92%
“…Our study did not focus on the role of symbionts, even though Symbiodiniaceae also includes generalists and specialists (Baker, 2003). For example, a coral host harbouring a generalist symbiont may show higher niche acclimatization due to the symbiont's greater physiological tolerances (Butler et al, 2023;Ziegler et al, 2015) and therefore can occupy wider ranges and large habitat gradients, but remains a symbiont specialist (Osvatic et al, 2021). Future systematic assessments of Symbiodiniaceae flexibility and its impact on coral ecology are essential.…”
Section: And Future Directionsmentioning
confidence: 99%
“…Experimental evolution has successfully enhanced the thermotolerance of multiple marine microalgal species in vitro (Chan et al, 2021), including Cladocopium proliferum (Butler et al, 2023;Chakravarti et al, 2017). Recent studies have shown that some heatevolved C. proliferum strains can enhance coral bleaching tolerance in larvae and juveniles (Table 1).…”
Section: Higher Thermotolerance Is Generally Seen In Corals Hostingmentioning
confidence: 99%